Disparity in Sentencing in Premeditated Murder Crimes to Provide Justice in Indonesia - Gulo, Cornelius Dikae Zolohefona; Fahrurrozi, Fahrurrozi; Aviva, Faradistia Nur; Arkanbariq, Anantya Aliyya (Universitas Muhammadiyah Yogyakarta, 2024)
Sentencing disparity is the imposition of different punishments for similar criminal acts without justification. Disparity of punishment is also found in several judges' decisions regarding premeditated murder, for example, Cassation Decision No. 1727 K/PID/2009 and Cassation Decision No. 922 K/Pid/2018. The two verdicts, in principle, addressed the case of premeditated murder; however, they rendered disparate and quite lame sentences for each defendant. This study aims to examine the punishments associated with criminal offenses and the factors causing the disparities in sentencing for premeditated murder in Indonesia. This study constitutes doctrinal legal research that examines secondary data, specifically judicial verdicts and legal statutes about premeditated murder. This study revealed that criminal sanctions were initially designed to inflict suffering on perpetrators who committed crimes. Ultimately, the objective of the sanctions evolved into a mechanism for educating perpetrators to prevent the recurrence of their actions. This study identified factors that cause disparities in sentencing for premeditated murder in Indonesia, precisely the defendant's type of culpability, motives and intentions behind the crime, intrinsic characteristics of the defendant, how the defendant executed the criminal act, and the potential impact of the sentence on the defendant's future. These factors can become sentencing guidelines that can serve as a guide and control for judges in formulating and imposing sentencing verdicts so that the sentencing can provide justice for all parties, both for victims, defendants, and the wider community.